Using solo and small ensemble instruction to promote lifelong engagement in music by challenging the large ensemble method of orchestra instruction through P.A.R. - Zeleski, S. Justin (Kansas State University, 2022)
High School graduation often marks a point where students, who have participated in music, drop out of participation. Misconceptions, inequitable skill development, and an overemphasis on semi-professional large ensembles continue to perpetuate this problem. This 7-month qualitative study in Millard, Nebraska used Participatory Action Research (PAR) to develop, implement, and empower students to become independent musicians by closing a null curriculum centered around the exclusion of solo preparation and small ensemble instruction. Over the span of eight weeks, students engaged in self-directed learning during the class period after which they answered surveys and interview questions to get to the heart of their experience. The results indicated that students enjoyed participating in the unit and developed practical skills that all independent musicians use while simultaneously maintaining the mandated school curriculum and large ensemble expectations. Limitation of schedule, demographics, and SES invite opportunities for further research while curricular recommendations can provide a foundation for future curriculum development centered around skill acquisition, student-directed education, and lifelong learning.
Keywords: Lifelong engagment; PAR; YPAR; Action research; Solo; Small ensemble; Music curriculum; Change theory; Experiential learning; Lewin; Kolb; Kratus